Peculiarities of the Use of Professionally Oriented Vocabulary by Future Agrarians while Learning English - Malyk, Valentyna (Educational Challenges, 2024)
The article is devoted to the study of the peculiarities of bilingualism of students of non-linguistic specialties when learning English. The terminological vocabulary allows accurate and accessible presentation of a content of this subject area and ensures correct understanding of the text. To represent the relations of information units (represented in terms), commonly used words are needed, which requires the use of ordinary language and leads to an appearance of ambiguity during their use.Purpose. The objective of study is consideration of linguistic particularities of agrarian professionally oriented vocabulary, which is used while studying a foreign language at the university.The methodology covers a comprehensive set of theoretical and empirical research methods, including the analysis of scientific sources, regulatory documents, pedagogical observation, description, classification and systematization. The study was related to students of the second year of full-time study of the agronomy specialty in Vinnytsia National Agrarian University, Ukraine.Results. The fact that the terms carry the main semantic load that in the literature of the agrarian direction, occupying the main place among other general literary and official words, is illustrated with examples. A detailed (conceptual) description of the agrarian industry has been carried out. It is noted that English-language agronomic texts differ in syntactic structure and complexity and are characterized by adverbial, infinitive and gerund inflections, as well as other purely language constructions, which in turn complicate text understanding and pose additional challenges to a translator. It is proved that the dictionary of agricultural terms is replenished by borrowing lexical units from everyday speech and by reinterpreting or narrowing their meanings. It is indicated that the colloquial language is enriched due to the expansion of the meanings of special terminological units. This dynamic two-way process testifies to a language development and translation complication activity due to the need to select the appropriate translation variant of multi-meaning lexical units.The investigation concluded that the clustering of many terminological constructions requires a correct division into immediate components and a serious familiarization with reference materials, a deeper immersion in the subject area. It is shown that agrarian terminology needs careful lexical and grammatical analysis in order to determine the optimal ways of its use. However, terminology alone is not sufficient to transfer or disseminate knowledge, as knowledge is culturally defined in human society.
Keywords: bilingualism; foreign language communicative culture; multilingual environment; professionally oriented vocabulary; term